Environmental Security and Environmental Management: The Role of Risk Assessment - Morel, Benoit; Linkov, Igor.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The concept of "Environmental security" has emerged as one basis for understanding international conflicts. This phrase can mean a variety of things. It can signify security issues stemming from environmental concerns or conflicting needs, or it can mean that the environment is treated as a resource for the long term, and the question is what should be done today to preserve the quality of the environment in the future. Over the last several years, the authors of this book and their colleagues have demonstrated the power and value of risk assessment and decision analysis as tools that decision makers should use for a broad range of environmental problems, including environmental security. This book is based on the discussions and papers prepared for the NATO Advanced Research Workshop that took place in Eilat, Israel, in April 2004. Many of the contributions in the book do not deal directly with the region, instead, they apply a risk analytical approach to a variety of environmental problems. The goal was as much to inform about the problems as it was to show the power of risk analysis as a tool to discuss environmental policy.
Environmental Security -- ENVIRONMENTAL SECURITY, CRITICAL INFRASTRUCTURE AND RISK ASSESSMENT: DEFINITIONS AND CURRENT TRENDS1 -- SECURITY AND THE ENVIRONMENT IN THE MIDDLE EAST WATER ISSUES -- POTENTIAL OF SOLAR THERMAL DESALINATION TO DEFUSE WATER AS A CONFLICT ISSUE IN THE MIDDLE EAST Proposal for Functional Cooperation in the Gulf of Aqaba -- WATER RESOURCES MANAGEMENT AND ENVIRONMENTAL SECURITY IN MEDITERRANEAN TRANSBOUNDARY RIVER BASINS -- THE ROLE OF COMPARATIVE RISK ASSESSMENT IN DECISION ANALYSIS MARSHLANDS OF MESOPOTAMIA AND AFFECTED RIPARIAN COUNTRIES -- A FUTURE FOR THE DEAD SEA BASIN: OPTIONS FOR A MORE SUSTAINABLE WATER MANAGEMENT -- ARE STANDARD RISK ACCEPTABILITY CRITERIA APPLICABLE TO CRITICAL INFRASTRUCTURE BASED ON ENVIRONMENTAL SECURITY NEEDS?1 -- FROM GLOBAL WARMING TO WATER SCARCITY: WHAT ARE THE MOST URGENT ENVIRONMENTAL PROBLEMS OF THE REGION. Report of the Discussion Group on Environmental Security -- Environmental Security, Critical Infrastructure and Risk Assessment: Definitions and Current Trends -- Environmental Management -- THE INTERCONNECTION BETWEEN THE BUILT ENVIRONMENT ECOLOGY AND HEALTH -- Security and the Environment in the Middle East Water Issues -- Potential of Solar Thermal Desalination to Defuse Water as a Conflict Issue in the Middle East -- Water Resources Management and Environmental Security in Mediterranean Transboundary River Basins -- The Role of Comparative Risk Assessment in Decision Analysis Marshlands of Mesopotamia and Affected Riparian Countries -- A Future for the Dead Sea Basin: Options for a More Sustainable Water Management -- Are Standard Risk Acceptability Criteria Applicable to Critical Infrastructure Based on Environmental Security Needs? -- From Global Warming to Water Scarcity: What Are the Most Urgent Environmental Problems of the Region -- The Interconnection between the Built Environment Ecology and Health -- Statistical Models for Distributions of Ambient Fine Particulate Matter -- QND: A Scenario-Based Gaming System for Modeling Environmental Processes and Management Decisions -- Mapping of Relative Risk -- Understanding Risk Culture and Developing a' soft' Approach to Risk Assessment Methodologies -- Different Preventive Strategies Require Diversified Risk Assessment Models -- Coupling Public Participation and Expert Judgment for Assessment of Innovative Contaminated Sediment Technologies -- Environmental Risk Assessment and Management: Promoting Security in the Middle East and the Mediterranean Region -- Reuse of Wastewater in Agriculture- Economic Assessment of Treatment and Supply Alternatives as Affecting Aquifer Pollution -- Minimizing the Risks Associated with Water Scarcity -- Integrated Risk-Based Management of Water Resources in the Jordan River Basin -- Outcome of NATO Workshop on Radiological Risk in Central Asia -- Public Transport Policy & Measures That Could Improve the Air Quality in Major Cities in Syria -- Modeling the Combination of Impacts Caused by Waste Heat Discharge from Power Plant Cooling Systems into Offshore Environments -- Role of Synergy in Biological Risk Assessment -- Cooperative Network for Environmental Risk Analysis Studies: The Case of the Middle East Region.
Keywords: ENVIRONMENTAL SCIENCES; LIFE SCIENCES; ENVIRONMENTAL MANAGEMENT; ENVIRONMENTAL TOXICOLOGY; ECONOMICS; ENVIRONMENT; ENVIRONMENTAL MANAGEMENT; ECOTOXICOLOGY; ECONOMICS/MANAGEMENT SCIENCE, GENERAL; LIFE SCIENCES, GENERAL; ENVIRONMENTAL MONITORING/ANALYSIS.